Assessing the Reliability of Halal Certification Implementation: A Qualitative Study on Perceptions of Halal Supervisors and Micro Business Actors - Bima, Muhammad; Mohammad Nizarul Alim; Adnan, Nurul Ilyana Muhd (Universitas Muhammadiyah Surakarta, 2025)
The potential for a critical point in the food and beverage sector has led to the emergence of a crucial role in the halal industry. This research aims to examine more deeply the halal industry governance system in micro and small businesses in the food and beverage sector by reviewing the legal perspective of the halal product guarantee system in the Bangkalan and Surabaya areas, as well as diagnosing the halal certification of micro and small businesses after obtaining a halal certificate. This research uses the phenomenological method by collecting primary data through interviews with informants, namely two business actors and one halal supervisor from the Halal Inspection Institute. Researchers also took data from focus group discussions with the Halal Product Guarantee Organizing Agency. The research results show that micro and small business actors consistently implement a halal product guarantee system by the provisions of the halal product guarantee system law. Apart from meeting halal standards, business actors also emphasize the importance of maintaining product quality at every stage of the production chain. This research also found that after halal certification was issued, micro and small businesses continued to make improvements and breakthroughs to ensure product quality and halalness were maintained throughout production. This research does not explore the social and economic factors of micro and small business actors in obtaining halal certificates. However, this research provides a perspective on consistently implementing halal governance by the halal product guarantee system law, which can help increase quality values.